IRB Oversight of Patient-Centered Outcomes Research: A National Survey of IRB Chairpersons. (October 2018) - Weissman, Joel S.; Campbell, Eric G.; Cohen, I. Glenn; Lynch, Holly Fernandez; Largent, Emily A.; Gupta, Avni; Rozenblum, Ronen; Abraham, Melissa; Spikes, Karen; Fagan, Maureen; Carnie, Martie
Patient-centered outcomes research (PCOR) is becoming increasingly common. However, there is little evidence regarding what novel ethical challenges, if any, are posed by PCOR with relevance to institutional review board (IRB) oversight and human subjects protections. This article reports the results of a national survey of all IRB chairpersons from research-intensive institutions in the United States. Findings address the responsibilities of IRBs and the challenges associated with PCOR review and oversight. IRB chairpersons varied in their judgment of PCOR's overall value to the scientific enterprise and to research at their institution. Furthermore, 27% of respondents considered patients serving in nontraditional roles to be research subjects even when they are not enrolled in research. There was also variation in the training and safeguards their IRBs require for patient partners. Our results suggest that guidance should be developed around ethical and regulatory issues associated with PCOR oversight.